Mobilidade de trabalhadores qualificados nas empresas inovadoras brasileiras - Macedo, Letícia Aparecida dos Santos (Universidade Federal de São Carlos, 2021)
The innovative process is uncertain and complex. Thus, knowledge becomes a relevant input for innovate activities. In addition to formal knowledge, it is important for innovation, stand out the tacit form, that acquired over time and that it not easily shared by formal process. In this context, assuming that people are the major carriers of tacit knowledge, the mobility of workers is essential to enable exchanges, thus possibility opportunities for knowledge transfers that impact on innovation. The present study aims are to analyze the mobility of skilled workers in Brazilian innovative companies in two specific trienniums and measure the influence of the mobility of skilled workers on innovation. Skilled workers were classified as employees with higher education or in occupations potentially linked to the areas of science and technology (POTEC). Initially, a descriptive analysis about the profile of companies considered to be innovate and of their employees was carried out between the years 2006 and 2011. After that, measure the skilled mobility workers was construed at the firm level in the sectors of extractive industry, transformation industry and electricity and gas. The GLM model with Poisson and Binomial Negative distribution and the TOBIT model were estimated. In the estimations, patent applications by company (dependent variable) were used as an innovation proxy. Skilled mobility of workers between companies was the independent interest variable. The results showed that the mobility of skilled workers is significant and positively impacts in innovation of companies. This result corroborates the importance of knowledge in innovative activities, seeing when moving, the worker increases the possibilities of knowledge exchange via face-to-face contact, in addition to generating new opportunities for access to different contact networks. Furthermore, it was found that the impact of mobility on innovation by POTEC workers is greater than that of workers with higher education.
Mobility of skilled workers in innovative Brazilian companies
Keywords: Mobilidade de trabalhadores qualificados; inovação; conhecimento; mobility of skilled workers; innovation; knowledge; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA